2(-5-3a)=7a+3

Simple and best practice solution for 2(-5-3a)=7a+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(-5-3a)=7a+3 equation:


Simplifying
2(-5 + -3a) = 7a + 3
(-5 * 2 + -3a * 2) = 7a + 3
(-10 + -6a) = 7a + 3

Reorder the terms:
-10 + -6a = 3 + 7a

Solving
-10 + -6a = 3 + 7a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-7a' to each side of the equation.
-10 + -6a + -7a = 3 + 7a + -7a

Combine like terms: -6a + -7a = -13a
-10 + -13a = 3 + 7a + -7a

Combine like terms: 7a + -7a = 0
-10 + -13a = 3 + 0
-10 + -13a = 3

Add '10' to each side of the equation.
-10 + 10 + -13a = 3 + 10

Combine like terms: -10 + 10 = 0
0 + -13a = 3 + 10
-13a = 3 + 10

Combine like terms: 3 + 10 = 13
-13a = 13

Divide each side by '-13'.
a = -1

Simplifying
a = -1

See similar equations:

| x^3+8x^2-8x-64= | | ln(x+3)-ln(x-4)=ln(x) | | -32x^2-80x-32=0 | | 3(r+4)+2(r+5)=32 | | 3x-5y=22 | | 15n^2+16n-7=0 | | (9x-2)(9x+2)= | | 27x^3+1000=0 | | -9=2-(5-z) | | 7x^2+-14x-7=0 | | 4+30(12+36+60)=x | | -4(6-w)=-2w-12+4w | | 0.8b=10.4 | | 1+3(16-2x)=0 | | 1+3(16-2x)= | | x+15=-5 | | x^2-24x+108=0 | | 9=-5(4x+2)+21x | | 4x=5y-17 | | .75w+8=.3w-7 | | -2(2+5n)+16(5-9n)= | | -30=j | | 6a^2+6a=6+6a | | 14=j-44 | | x=3.14(36)8-3.14(16)8 | | 4x^2-48x+25=0 | | 64x^2+144x+81=0 | | a^2+6a=1-a | | x=3.14(12)1.5(1.5)+2(.5)3(4) | | -2(x+3)+3x=15 | | 3t^2=16 | | 7-2a=-5 |

Equations solver categories